2005
DOI: 10.1097/01.ju.0000154343.35444.09
|View full text |Cite
|
Sign up to set email alerts
|

OVER EXPRESSION OF HYPOXIA-INDUCIBLE FACTOR-1α IN RENAL AND BLADDER CANCER CELLS INCREASES TUMORIGENIC POTENCY

Abstract: These results suggest that HIF-1alpha may have important roles in bladder and renal cancer angiogenesis and proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 13 publications
2
22
0
Order By: Relevance
“…These results underscore the importance of HIF activation for cell proliferation and tumor progression in these cell lines. This is consistent with previous observations that the activation of HIF activity through its overexpression (28) or chronic hypoxia (52) leads to increased tumor growth. Conversely, decreasing HIF transcriptional activity through antisense, dominant-negative, or short interfering RNA constructs (12,14,27,30,39) slows tumor progression.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results underscore the importance of HIF activation for cell proliferation and tumor progression in these cell lines. This is consistent with previous observations that the activation of HIF activity through its overexpression (28) or chronic hypoxia (52) leads to increased tumor growth. Conversely, decreasing HIF transcriptional activity through antisense, dominant-negative, or short interfering RNA constructs (12,14,27,30,39) slows tumor progression.…”
Section: Discussionsupporting
confidence: 82%
“…Some evidence suggests that the flavin adenine dinucleotide site in SdhA is the principal source of superoxide generation, due to the exposure of VOL. 28,2008 SdhB DISRUPTION ALTERS ROS, HIF, AND TUMOR GROWTH 727…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the resulting HIF-1␣ ϩ/ϩ tumors grew significantly faster than HIF-1␣ Ϫ/Ϫ tumors. In line with these studies, an in vivo experiment by Kondo et al [84] suggested that overexpression of HIF-1␣ increased the tumor growth of renal cancer cells in nude mice. In contrast, Savai et al [85] concluded that, in subcutaneous tumors derived from HIF-1␣-overexpressing A549 cells, tumor growth was negatively affected as a result of decreased proliferation and increased apoptosis.…”
Section: Hypoxia and Tumor Growthsupporting
confidence: 54%
“…The formation of tumor microvessels is stimulated by angiogenic factors, especially vascular endothelial growth factor (VEGF) [3][4][5] . Hypoxia is related to tumor cell growth, differentiation, invasion and metastasis activity.…”
Section: Introductionmentioning
confidence: 99%